Hepatoprotective and antioxidant effect of curcumin on sleep deprived albino rats. - SALIHA C.K,; SANDHYA T AVADHANY, (International Journal of Pharma and Bio Sciences, 2018)
In this study, changes in the antioxidant level and histopathological parameters in acute and chronic sleep deprived rats were evaluated. Effect of curcumin on sleep deprivation induced liver damage was also examined in this study. Thirty male albino rates were examined for the study. Selected stress markers were reduced glutathione (GSH) and malondialdehyde (MDA). All the markers showed significant changes in both acute and chronic groups. Pretreatment of curcumin showed a significant improvement in acute sleep deprived group but the changes were not significant in the chronic group. Histopathological findings also support the biochemical findings. These results suggest that sleep deprivation can lead to oxidative stress damage in liver and dietary intake of curcumin can improve the antioxidant level in the body and reduce the risks caused by sleep deprivation.